MEASURING THE EFFECT OF URBAN IMAGE DIMENSIONS ON BEHAVIORAL INTENTIONS FOR A CITY: ANKARA EXAMPLE (Third Sector Social Economic Review, 2017)
The purpose of this study is to determine the effective dimensions of urban image on the behavioral intention and to reveal the effect of these dimensions on behavioral intention. The study was carried out using the structural equation model. 400 people participated in the study. According to the results of the study, the city image dimensions of tourism and entertainment, livability, security were found to be effective on behavioral intention.
Keywords: City İmage; Ankara